Correlation Between Leg Muscle Explosive Power and Futsal Shooting Ability - Fiko Putra Wardhana Wardhana; Agus Darmawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the relationship between the explosiveness of the leg muscles and the ability to shoot futsal in students participating in futsal extracurricular at SMP Muhammadiyah 3 Semarang. The research uses a quantitative approach with a correlational descriptive design. The research population amounted to 40 male students who actively participated in futsal extracurriculars with sampling techniques using total sampling. The data collection instruments included a vertical jump test to measure the explosiveness of leg muscles and a shooting test to measure futsal shooting ability. The data analysis technique used descriptive statistics, Shapiro-Wilk normality test, Pearson Product Moment correlation test, and determination coefficient analysis. The results of the study showed a significance value of 0.000 < 0.05 which means that there is a positive and significant relationship between the explosive power of the leg muscles and the ability to shoot futsal. The value of the correlation coefficient of 0.539 is included in the category of medium relationships. In addition, the determination coefficient value showed that the explosive power of the leg muscles contributed 29.1% to shooting ability. The study's findings show that students who have better leg muscle explosiveness tend to have stronger and more accurate shooting. Therefore, coaches are advised to implement a training program that focuses on increasing the explosiveness of the leg muscles to improve students' futsal shooting skills.